9514 1404 393
Answer:
A. f^-1(x) = x³ -12
Step-by-step explanation:
The inverse function can be found by solving ...
x = f(y)
x = ∛(y +12) . . . . . use the definition of f(x)
x³ = y +12 . . . . . . . cube both sides to eliminate the radical
x³ -12 = y . . . . . . . add -12 to isolate the y-variable
f^-1(x) = x³ -12 . . . matches choice A
1,710/3 = 570 <== this is just simple division...nothing a calculator can't do.
Answer:
That would be sina.
Step-by-step explanation:
sin(a+b) = sinacosb + cosasinb
sin(a-b) = sinacosb - cosasinb
Adding we get sin(a+b) + sin(a-b) = 2sinaccosb
so sinacosb = 1/2sin(a+b) + sin(a-b)
The simplified expression of 2√8x³(3√10x⁴ - x√5x²) is 24x³√5x - 4x³√10x
<h3>How to determine the simplified product?</h3>
The complete question is added as an attachment
From the attached figure, the product expression is:
2√8x³(3√10x⁴ - x√5x²)
Evaluate the exponents
2√8x³(3√10x⁴ - x√5x²) = 2 *2x√2x(3x²√10 - x²√5)
Evaluate the products
2√8x³(3√10x⁴ - x√5x²) = 4x√2x(3x²√10 - x²√5)
Open the bracket
2√8x³(3√10x⁴ - x√5x²) = 12x³√20x - 4x³√10x
Evaluate the exponents
2√8x³(3√10x⁴ - x√5x²) = 24x³√5x - 4x³√10x
Hence, the simplified expression of 2√8x³(3√10x⁴ - x√5x²) is 24x³√5x - 4x³√10x
Read more about expressions at:
brainly.com/question/12990602
#SPJ1
Outer Square perimeter minus inside perimeter equals outside square perimeter